A Rare Complication of Tracheal Intubation: Tongue Perforation - Loreto Lollo; Tanya K. Meyer; Andreas Grabinsky (Case Reports in Anesthesiology)
Aim. To describe the subsequent treatment of airway trauma sustained during laryngoscopy and endotracheal intubation. Methods. A rare injury occurring during laryngoscopy and endotracheal intubation that resulted in perforation of the tongue by an endotracheal tube and the subsequent management of this unusual complication are discussed. A 65-year-old female with intraparenchymal brain hemorrhage with rapidly progressive neurologic deterioration had the airway secured prior to arrival at the referral institution. The endotracheal tube (ETT) was noted to have pierced through the base of the tongue and entered the trachea, and the patient underwent operative laryngoscopy to inspect the injury and the ETT was replaced by tracheostomy. Results. Laryngoscopy demonstrated the ETT to perforate the base of the tongue. The airway was secured with tracheostomy and the ETT was removed. Conclusions. A wide variety of complications resulting from direct and video-assisted laryngoscopy and tracheal intubation have been reported. Direct perforation of the tongue with an ETT and ability to ventilate and oxygenate subsequently is a rare injury.